PERSEPSI WARGA BELAJAR TERHADAP PROGRAM PAKET C DI PKBM INSAN CENDIKIA KELURAHAN SIALANG MUNGGU KECAMATAN TAMPAN KOTA PEKANBARU - B.Gusti Er Dola; Titi Maemunaty; Widiastuti Widiastuti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is motivated by the C Program Package at Community Learning Center (PKBM) seen from the time discipline is quite good, because the teachers come on time. Implementation for the Package C Program at the Community Learning Center (PKBM) is good because the teachers are professional teachers in teaching. Teachers of educators or tutors who teach in the Package C Program at the Community Learning Center (PKBM) are good, because the teachers have mastered learning in accordance with the objectives. Evaluation for the C Program Package at Community Learning Activities Center (PKBM) is felt good, because one way the tutor evaluates the learners by looking at the attitude of the learning community. The formulation of this research problem is whether the perception of citizens studying the C package program in PKBM Insan Cendikia Sialang Munggu Kecamatan Tampan Pekanbaru is quite good. The purpose of this study is to determine the perceptions of studying citizens of the C package program in PKBM Insan Cendikia Sialang Munggu Village Tampan District Pekanbaru city is good. . The population that is taken in this research is Citizens LearningPaket C PKBM Insan Cendikia Sialang mungguKecamatan Tampan Kota Pekanbaru, amounting to 45Warga Belajar. Researchers determine the sample of 45 Residents LearningPaket C in PKBM Insan Cendikia Sialang mungguKecamatan Tampan Kota Pekanbaru and 20 residents learn Packet C for trials in PKBM Riau Jaya Cemerlang using saturated sampling technique. Instrument in this research is a questionnaire that contains statements about the perceptions of citizens learning Packaged C in PKBM Insan Cendikia Sialang munggukecamatan Tampan Kota Pekanbaru. The conclusion of this study is that indicators of learning program is the highest indicator compared to other indicators, because citizens have a good view of creative teachers in teaching.Keywords: Student perception of learning and Package C program